A Comprehensive Entrepreneurship Education Model Based on Social Cognitive Theory - Christina; Handyanto Widjojo (Universitas Airlangga, 2023)
Objective: This study examines entrepreneurship education's effect on entrepreneurial mindset, competencies, and intention. Design/Methods/Approach: This study uses a quantitative approach, applying structural equation modeling using PLS to verify the hypothesis relationship. Data is collected from 281 college students who have finished at least one semester of any entrepreneurship subject. Findings: The findings indicate that entrepreneurship education significantly affects entrepreneurial mindset, competencies, and intention. Entrepreneurial competencies significantly affect entrepreneurial intention. Meanwhile, an entrepreneurial mindset insignificantly affects entrepreneurial intention. Originality: This research offers a comprehensive model using a new perspective of the social cognitive theory that investigates the impact of entrepreneurship education on entrepreneurial mindset, competencies, and intention, whereas most research on entrepreneurship education and intention use the theory of planned behavior. This study is expected to fill the gaps in understanding the connection between entrepreneurship education and entrepreneurial intention from a different angle. Practical/Policy implication: Given the results, entrepreneurship education should build entrepreneurial competencies that drive students' entrepreneurial intentions.